The Adaptive Learning Effects in Developing Coercive Digital Leadership: Efforts to Improve Lecturer Performance in Central Java Province Through Integration of Transformational Leadership, Power and Digital Intellectuality - Ratih Pratiwi; Yudithia Dian Putra; Iswati Iswati (PT Mattawang Mediatama Solution, 2022)
Developing a holistic business management model that guarantees transformation and high technology-based organizations are carried out for sustained value generation and global competitiveness may provide an organization with a competitive edge. This study's objective was to investigate the performance development model of lecturers at private Islamic institutions in Central Java, which is based on coercive digital leadership and adaptive learning. This research approach employs